Estabilidade de taludes em terraços agrícolas na Região Demarcada do Douro : modelação de base estatística - Oliveira, Ana (2015)
The evaluation of the slope instability in agricultural terraces in the Douro Region (Quinta das Carvalhas) was done by two statistical based methods - Logistic Regression and Information Value Method based on the statistical correlation between the occurrences (dependent variable) and the conditioning factors (independent variables). As conditioning factors were considered the slope, curvature and aspect, contributing areas, the relative humidity, the slope of the agricultural terrace riser and land use. The variables related with the agricultural terraces structures and land use were obtained by vectorization based on orthophotomap with a resolution of 50 cm. The field camping carried out 329 instability record points. Two scenarios were considered through two elevation models (with a resolution of 5 meters) constructed with different base information: one from contours (scale 1: 25,000) with contour interval of 10 m, spot heights and 3D hydrographic network, and another from aerial photographs with a resolution of 50 cm. 50% of the inventory was used in the modelling and the other half was used to validate with the use of contingency tables. The DTM A Information Value method has the best validation with a value of 5:22 in relation True Positive Rate (TPR)/False Positive Rate (FPR).